Atroposelective construction of axially chiral alkenylindole-fused nine-membered rings via catalytic asymmetric formal (4 + 5) cycloaddition - Si-Jia Liu; Xue Wang; Ji-Xiang Yang; Xian-Song Ao; Shao-Fei Ni; Yu-Chen Zhang; Feng Shi (Nature Communications)
Abstract Catalytic atroposelective construction of axially chiral aryl-fused medium-sized rings, particularly nine-membered rings, is of great importance but with enormous challenges. To overcome these challenges, in this work, the catalytic atroposelective construction of axially chiral arylalkene-fused nine-membered rings has been established, which makes use of organocatalytic asymmetric formal (4 + 5) cycloaddition of 3-alkynyl-2-indolylmethanols with 2-indolylethanols. By this strategy, various axially chiral alkenylindole-fused nine-membered rings were constructed in high enantioselectivities with moderate to good yields (up to 74% yield, 98% ee). Theoretical calculations provide an in-depth understanding on the reaction pathway and activation mode of the organocatalytic asymmetric formal (4 + 5) cycloaddition, and application explorations demonstrate the great potential of these axially chiral arylalkene-fused nine-membered rings in asymmetric catalysis and medicinal chemistry. Besides, this strategy could be extended to organocatalytic formal (4 + 4) cycloaddition of 3-alkynyl-2-indolylmethanols with 2-indolylmethanols. This work has not only realized the organocatalytic asymmetric formal (4 + 5) cycloaddition, but also provided an efficient strategy for the synthesis of axially chiral aryl-fused nine-membered rings, which will greatly advance the chemistry of cycloadditions and atropisomers.